Sinus mucosa thinning and perforation after sinus augmentation. A histological study in rabbits - Kato, Shingo; Botticelli, Daniele; De Santis, Enzo; Kanayama, Masatsugu; Ferreira, Sabrina [UNESP]; Rangel-Garcia Jr, Idelmo [UNESP] (Springer Nature, 2021)
Aim: To evaluate the modifications and possible perforations of the sinus mucosa lining graft particles and implant surfaces after sinus lifting. Material and methods: Twelve New Zealand rabbits underwent a bilateral sinus lifting using either autogenous bone harvested from the tibia (AB; autogenous bone group) or deproteinized bovine bone mineral (DBBM group) as filler. Implants were simultaneously installed. Thinned sites (<40 μm) and perforations were histologically evaluated at the sinus mucosa in contact with the graft and with the implant after 7 and 40 days of healing. Results: The mean width of the pristine mucosa was ~70–80 μm. After 7 days of healing, the sinus mucosa in contact with the graft presented fourteen thinned sites in the AB group (mean width 28.8±12.8 μm) and fifty-nine in the DBBM group (mean width 22.2±5.2 μm). No perforations of the mucosa were seen in the AB group while six perforations distributed in two sinuses were found in the DBBM group. After 40 days, only one thinned mucosa and no perforations were observed in the AB group while ninety-six thinned mucosa sites were shared by six sinuses (19.2±3.8 μm), and 3 perforations by two sinuses in the DBBM group. Few sites of the mucosa were in contact with the implant apex and threads after 7 days of healing. However, after 40 days, twelve thinned mucosa sites were seen in four sinuses in the AB groups (mean width ~19 μm) and 5 in two sinuses in the DBBM group (mean width ~20 μm). Perforations were seen in two sinuses in the AB group, and in one sinus in the DBBM group. Conclusions: The sinus mucosa might be damaged by a close contact with graft particles and implant surface.
Keywords: Animal study; Bone healing; Perforation; Sinus floor elevation; Xenograft